Characteristics of Effective Trade Secrets and Confi dential Information Policies: Guidance from Labor Arbitration Cases - Ross, William H.; Franklin, Danny (Labor Law Journal, 2020)
In an effort to craft recommendations to managers regarding effective confidential information policies, the present paper reviewed 88 published grievance arbitration cases involving proprietary information, trade secrets, and confidential information. Most cases dealt with the application of managerial discipline for employee violations of company polices and collective-bargaining provisions. Themes that emerged included: the importance of a Management Rights clause (as well as specific Misconduct clauses and policies), clauses that address changing business conditions (such as subcontracting and new technology), employee insubordination, theft, falsification, conflict of interest, and the need for training. Additionally, arbitrators often considered specific laws that apply in health care, cable television, and telecommunications industries. Finally, several mitigating factors were noted such as: having permission from a supervisor to access confidential information, safety, and whistleblowing concerns. By attending to factors that influence arbitrator decision making, managers and their attorneys can use these identified factors to create better policies and negotiate robust collective bargaining provisions.
Num Pages: 43-57 Place: Riverwoods, United States Publisher: CCH Incorporated: Health & Human Resources
Keywords: Arbitration; Business And Economics–Labor And Industrial Relations; Collective bargaining; Competition; Competitive advantage; Conflicts of interest; Discipline; Employees; Espionage; Fair & Accurate Credit Transactions Act 2003-US; Information policies; Intellectual property; Labor law; Law; dept.mgt

The Effect of Higher Education on Youth Unemployment in European Regions During a Period of Economic Instability - Hermannsson, K.; Scandurra, R.; Graziano, M. (Journal of Education Finance, 2020)
This paper examines the impact of higher education on youth unemployment. Following the 2008 financial crisis, youth unemployment returned to the fore as a serious concern among policy makers in Europe. A crucial difference from previous recessions is that this time around supply of higher education opportunities was much higher than in the 1980s, and indeed higher education participation rates grew rapidly in many regions during this period. Drawing on previous work on youth unemployment and the economic impacts of education we identify a variety of channels through which higher education is likely to influence youth unemployment. We examine this issue using a macro-panel of European regions for the period 2002-2012. This decade was characterized by variation in economic activity and higher education rates. Our results suggest that expansion of higher education during this period had a mitigating effect on youth unemployment and not recognizing this external benefit of education risks underestimating the effects of macroeconomic shocks on young people. © 2020, University of Illinois Press. All rights reserved.
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

A comparison of two multilingual meeting systems - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: Google Translate; dept.bis; dept.mgt; peer-reviewed

Thinkubator Approach to Solving the Soft Skills Gap - Stewart, Carol; Marciniec, Sheryl; Lawrence, Denval; Joyner-McGraw, Laquita (American Journal of Management, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

Uncovering Relations Between Leadership Perceptions and Motivation Under Different Organizational Contexts: a Multilevel Cross-lagged Analysis - Gagné, Marylène; Morin, Alexandre J. S.; Schabram, Kira; Wang, Zhe Ni; Chemolli, Emanuela; Briand, Mélanie (Journal of Business and Psychology, 2020)
Surprisingly scant research has adequately examined directional influences between different perceptions of managerial leadership behaviors and different types of work motivation, and even fewer studies have examined contextual moderators of these influences. The present study investigated longitudinal and multilevel autoregressive cross-lagged relations between perceptions of transformational, transactional, and passive-avoidant leadership with autonomous motivation, controlled motivation, and amotivation. Multilevel longitudinal models were estimated on data from 788 employees, nested under 108 distinct supervisors, from six Canadian organizations. Results revealed that perceptions of leadership behaviors predicted changes in motivation mostly at the collective level and that some of these relations changed as a function of whether organizations had recently faced a crisis. Collective perceptions of transformational leadership were related to increased collective autonomous and controlled motivation, while individual controlled motivation was related to increased individual perceptions of transactional leadership. In organizations facing a crisis, individual perceptions of transactional leadership were related to decreased individual controlled motivation, while collective perceptions of transactional leadership were related to increased collective autonomous motivation and decreased collective amotivation. In organizations not facing a crisis, collective perceptions of transactional leadership were related to decreased collective autonomous motivation. Implications for theory and practice are discussed.
11 citations (Crossref) [2023-10-31] tex.ids: gagneUncoveringRelationsLeadership2020, lens.org/066-744-892-590-102, pop00060 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85071718155 tex.type: [object Object] type: Article
Keywords: Autonomous motivation; Multilevel modeling; Transactional leadership; Transformational leadership; dept.mgt; peer-reviewed

Family Law and Practice - Luppino, Grace A.; Miller, Justine FitzGerald (Pearson, 2020)
For courses in family law for students in paralegal studies programs, broader legal studies programs, and those majoring in criminal justice, social work, and education. Connecting theory, history, and practice in family law Family Law and Practice prepares students to enter the workplace with a firm grasp of family law and procedural components of family law practice. To meet this challenge, the authors have divided the 5th edition into two parts: the first introducing the principles of family law and the second translating theory into practice. The new edition also addresses changing views on marriage, spousal roles, children’s status in the family, and even what constitutes a family. It also adds cases, statutes, and legal forms from a variety of US states to engage students across the country.
Keywords: Domestic relations; Handbooks; manuals; etc; United States; United States; Legal assistants; dept.mgt; faculty_collection